2005
DOI: 10.1590/s1516-35982005000400032
|View full text |Cite
|
Sign up to set email alerts
|

Recria de machos Nelore em pastagens cultivadas com suplementação na seca nos Cerrados do Brasil Central

Abstract: RESUMO -Foi avaliado, durante três anos, o desempenho de 103 bezerros Nelore criados a pasto, recriados com suplementação na primeira seca pós-desmama, com o objetivo de se obterem animais com desenvolvimento suficiente para serem confinados aos 20/21 meses de idade. Os animais apresentaram, início da suplementação, 189,51 ± 21,08 kg de peso vivo e 254 ± 29,22 dias de idade e, ao final, de 242,38 ± 29,22 kg e 400 ± 31,08 dias de idade e consumo médio diário de ração de 1,52 kg. Durante a suplementação, o ganho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
1
1
0
2
Order By: Relevance
“…A positive correlation was observed (r=0.49) between the initial weight in the growing stage and the initial weight in the feedlot stage (Table 5), supporting the results of Vieira et al (2005), who observed a positive correlation (r=0.70) between the initial weight and the weight at the end of supplementation during the growing stage of Nelore cattle. This finding emphasizes the importance of supplementation during the growing stage in order to obtain heavier animals at the beginning of the feedlot stage, because animals with feed restrictions at this stage rarely reach the initial weights, although they may have a compensatory gain.…”
Section: Tempo (Dias)supporting
confidence: 85%
“…A positive correlation was observed (r=0.49) between the initial weight in the growing stage and the initial weight in the feedlot stage (Table 5), supporting the results of Vieira et al (2005), who observed a positive correlation (r=0.70) between the initial weight and the weight at the end of supplementation during the growing stage of Nelore cattle. This finding emphasizes the importance of supplementation during the growing stage in order to obtain heavier animals at the beginning of the feedlot stage, because animals with feed restrictions at this stage rarely reach the initial weights, although they may have a compensatory gain.…”
Section: Tempo (Dias)supporting
confidence: 85%
“…Furthermore, higher productive performance in the early stages of the production cycle may shorten the fattening and finishing period of steers, with economic and environmental benefits (32,33) .…”
Section: Resultsmentioning
confidence: 99%
“…Do período pósdesmama até um ano de idade, os animais praticamente mantêm o peso, principalmente se manejados exclusivamente em pastagens. Na desmama, além da quebra da relação e dependência maternal, as crias normalmente são submetidas a severa restrição alimentar, com a diminuição da qualidade e quantidade das pastagens disponíveis (VIEIRA, 2005).…”
Section: Desmama De Bezerrosunclassified